Piperacillin-induced mild haemolytic anaemia in a 44-year-old patient with cystic fibrosis. (24th October 2016) - Meinus, Carolin; Schwarz, Carsten; Mayer, Beate; Roehmel, J F
Abstract : Piperacillin–tazobactam is an antipseudomonal antibiotic frequently used in patients with cystic fibrosis (CF) to treat pulmonary exacerbations. Drug-induced immune haemolytic anaemia is a rare complication during treatment with piperacillin. So far, piperacillin-induced immune haemolytic anaemia (PIHA) is regarded as an acute and severe haemolytic anaemia resulting into life-threatening events. Here we report on a patient with mild PIHA, which did not result in any clinical symptoms or necessity for treatment. To the best of our knowledge, this is the first case report of PIHA without an acute severe haemolytic anaemia. Further research is needed to clarify if this case is a solitary clinical manifestation of PIHA or if mild clinical courses of PIHA might be under-reported. Cases of PIHA have been largely reported in patients with CF. This unequal distribution maybe due to the frequent administration of piperacillin for pulmonary exacerbation in patients with CF or due to CF-related cofactors of yet unknown aetiology.